Teammate influences and relationship quality are associated with eating and exercise psychopathology in athletes. (1st December 2019) - Scott, Charlotte L.; Haycraft, Emma; Plateau, Carolyn R.
Abstract: Teammates have a powerful influence on athletes' eating attitudes/behaviours, but less is known about the relative importance of teammate influence mechanisms. The primary aim of this study was to explore the relationships and predictive associations between teammate influences (e.g., modelling of teammates' disordered eating; supportive teammate friendships) and athletes' eating and exercise attitudes and behaviours. A further aim was to identify the presence of any gender differences. Athletes (N = 1172, mean age 24 years, n = 727 female) completed a survey exploring multiple teammate influences, eating and exercise attitudes and behaviours, and psychological wellbeing (anxiety, depression, self-esteem). Many significant relationships were identified between teammate influences and eating/exercise psychopathology. Stepwise regression analysis revealed that a perceived pressure from teammates to lose weight/change shape and perceptions that teammates engaged in disordered eating practices were the best predictors of higher eating and exercise psychopathology. Supportive teammate friendships was the best predictor of lower eating psychopathology and higher levels of healthy exercise behaviours. Encouragement/discouragement to eat healthily were also significant predictors. Teammate influences explained more variance in exercise than eating psychopathology, and total variance explained by teammates was higher for females compared to males. Teammates may have a positive and negative influence on the eating and exercise attitudes/behaviours of athletes; however, gender differences are apparent. Understanding teammate influences on the eating and exercise practices of athletes is important for the development of team-based interventions to reduce or prevent disordered eating and exercise. Future research should explore these relationships longitudinally, considering the role of moderating factors (e.g., sport type, stage of season).